Chemically Stressed Bacterial Communities in Anaerobic Digesters Exhibit Resilience and Ecological Flexibility - Schwan, Benjamin; Abendroth, Christian; Latorre-Pérez, Adriel; Porcar, Manuel; Vilanova, Cristina; Dornack, Christina (Frontiers in Microbiology, 2020)
Anaerobic digestion is a technology known for its potential in terms of methane production. During the digestion process, multiple metabolites of high value are synthesized. However, recent works demonstrate the high robustness and resilience of the involved microbiomes, which makes it difficult to manipulate them in such a way that a specific metabolite is produced predominantly. Therefore, an exact understanding of the manipulability of anaerobic microbiomes might open up a treasure box for the bio-based industries. In the present work, the effect of nalidixic acid, Ɣ-aminobutyric acid (GABA), and sodium phosphate on the microbiome of digested sewage sludge from a water treatment plant, fed with glucose, was investigated. In spite of the induced process perturbations, a high stability was observed at the phylum level. However, strong variations were observed at the genus level, especially for the genera Trichococcus, Candidatus Caldatribacterium and Phascolarctobacterium. The analysis of microbial interactions, on the basis of the Lotka-Volterra model, revealed a surprisingly dynamic behaviour. Many of the involved genera dynamically shifted among positive, negative or no interaction, depending on the applied stressor. Globally, the presented work suggests a massive resilience and stability of the methanogenic communities coupled with a surprising flexibility of the particular microbial keyplayers involved in the process.